New approach for designing an underwater free-space optical communication system - Chen, Yanhu; Zhang, Luning; Ling, Yucheng (Frontiers in Marine Science, 2022)
Ocean observation system that involves multiple underwater vehicles and seafloor nodes plays an important role in better learning the ocean, where underwater wireless communication is mandatory for massive data interaction. Optical communication that has wide bandwidth and comprehensive working distance is the preferred method compared to acoustic and other methods. However, the presence of directionality makes the optical method difficult to use especially when the transceiver is equipped on a motive vehicle. In this study, an underwater free-space optical communication method of transmitting information is proposed. Characteristics of underwater optical transmission, as well as the photoelectric signal processing and modulation and demodulation algorithms, are studied and modeled. New approach for realizing underwater free-space optical communication is proposed and simulated. A prototype including a free-space optical transmitter and a receiver is developed; tests in different scenarios were carried out, and the results were observed: (1) by using the minimum number of LEDs, the effect of uniform lighting in space is achieved, and the transmitter coverage reaches 160°. (2) When the power of the transmitter is 10 W and the communication rate is 1 Mbps, the maximum communication distance reaches 13 m.